Nanomaterial based mass spectrometry of oligodeoxynucleotide–drug complexes. Issue 15 (7th August 2015) - Huang, Yu-Hui; Wang, Chia-Wei; Chen, Wen-Tsen; Chen, Li-Yi; Chang, Huan-Tsung
<x xml:space="preserve">Abstract</x> SALDI-MS has been applied to the detection of ODNs and MTX–ODN complexes using HgTe nanostructures as matrices.